KEBANGKRUTAN LEMBAGA PERKREDITAN DESA (LPD) BERDASARKAN ANALISIS BERBAGAI FAKTOR - Saputra, Komang Adi Kurniawan; Trisnadewi, A.A. Ayu Erna; Anggiriawan, Putu Budi; Kawisana, Putu Gede Wisnu Permana (Jurnal Ilmiah Akuntansi, 2019)
This study aims to examine several factors that influence the bankruptcy of LPDs in Buleleng Regency, the factors in question are legal protection, managerial competence, good corporate governance, the active role of citizens and the role of internal supervisory bodies. In this study using a questionnaire method with 63 respondents namely LPD managers and for data analysis use multiple regression analysis. The results of this study state that only the manager's competence and the role of internal supervisory bodies have an influence on the potential of LPD bankruptcy, while legal protection variables, good corporate governance and the active role of citizens do not affect the potential for bankruptcy LPD in Buleleng Regency.